2015
DOI: 10.1016/j.profoo.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Knowledge and Attitude on Food Colorant Uses of PKK Mothers in Penggaron Lor Village

Abstract: The problem in Penggaron Lor Village are the lack of knowledge and skills, especially mothers about healthy snacks and food colorant, so it requires to observed the the correlation between knowledge and attitude on food colorant uses. This study was an observational analytic study with cross sectional design. Among PKK (a community organization whose members mothers household), 57.9 % and 50 % (n=38) had a good level of food colorant knowledge and attitude, respectively. The improper food colorant uses are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
3
1
2
Order By: Relevance
“…Since attitude is the most important factor determining feeding behavior [ 28 ], the behavior of the mothers in Bushehr would improve by increasing their knowledge and aligning their attitude. However, this is inconsistent with the findings of Suparmi et al [ 34 ] who indicated that there was no relationship between knowledge and attitude.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Since attitude is the most important factor determining feeding behavior [ 28 ], the behavior of the mothers in Bushehr would improve by increasing their knowledge and aligning their attitude. However, this is inconsistent with the findings of Suparmi et al [ 34 ] who indicated that there was no relationship between knowledge and attitude.…”
Section: Discussioncontrasting
confidence: 94%
“…The results of the present study indicated a positive attitude towards food security in complementary feeding by the mothers. A study conducted in Indonesia by Suparmi et al [ 34 ] reported 50% positive feeding attitude of the mothers. According to Behroozeh et al [ 35 ], attitude is among the factors affecting food security that should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…However good knowledge of food safety did not necessarily lead to good handling practices (Bas et al, 2006). Furthermore, a negative correlation was found between practice with knowledge and attitude (Suparmi et al, 2015).…”
Section: Correlation Between Knowledge With Attitude and Practicementioning
confidence: 91%
“…The herbal origin allows the producers to extract pigments from a plant or a part of it, for instance, its leaves, roots, flowers, peels, or even fruits. In this regard, chemical interference risks with human health are minimized (Cortez et al., 2017 ; Martins et al., 2016 ; Mohamad et al., 2019 ; Neves et al., 2019 ; Özkan & Bilek, 2014 ; Rodriguez‐Amaya, 2019 ; Suparmi & Cahyono, 2015 ).…”
Section: Color Perceptionmentioning
confidence: 99%